Amorphizing of Ag Nanoparticles under Bioinspired One‐step Assembly of Fe3O4‐Ag/rGO Hybrids via Self‐redox Process with Enhanced Activity. (29th May 2018) - Zhao, Songfang; Jiang, Haobo; Li, Jinhui; Meng, Xiangying; Chao, Tianyu; Zhang, Zhe; Zhang, Peng; Gao, Yongju; Cao, Duxia
Abstract : Efficient and reusable nanocatalysts fabricated via a facile assembly are highly desirable for the cost‐effective hydrogenation reduction. Inspired by a fishing process with a fishnet, multifunctional nanostructured catalysts are rationally designed to combine interesting features via the self‐redox assembly of Fe3 O4 ‐Ag composites on reduced graphene oxide (rGO) (Fe3 O4 ‐Ag/rGO). In detail, Fe3 O4 nanoparticles (NPs) endow the ternary hybrids with superparamagnetism (21.42 emu g −1 ), facilitating catalysts to be separated from the reaction system. rGO could provide electron transfer pathways, enhancing catalytic activity. More interestingly, GO and Ag + could behave as oxidants to oxidize Fe 2+ for the in situ assembly of Fe3 O4 ‐Ag/rGO without any addition of reductant/oxidant or organic solvents, and AgNPs endow the ternary hybrids with excellent catalytic behaviour. Meaningfully, the bioinspired process enables the ternary hybrids to possess more abundant micro−/nanopores, larger surface area, and more amorphization. They exhibit exceptional catalytic performance, and could be recycled with excellent activity by means of convenient magnetic separation (at least 7 times). Moreover, the ternary hybrids could degrade methylene blue under UV light due to different valence states of Fe in Fe3 O4 . Therefore, the proposed bioinspired assembly and structure design for hierarchical catalysts would pave a promising way to assemble other catalysts. Abstract : The key novelty lies in no addition of other reductant or capping agents, and crystalline transformation of Ag NPs under bioinspired, one‐step assembly. The bioinspired process enables the ternary hybrids to possess more abundant micro−/nanopores, larger surface area, and more amorphization. The formation of amorphization could introduce more active sites, enhancing the activity.